Improving Sports Participation among Students through Mobile Application - Heng Zhuang Ching; Norfaradilla Wahid; Hanayanti Hafit; Shahreen Kasim (JOIV : International Journal on Informatics Visualization, 2018)
Technologies are advancing at incredible speed with great purposes. Unfortunately, as technologies grow, some people have lost their motivation to keep up with their health by neglecting their physical activities like sports, outdoor games, etc. There are less people willing to step outside to do physical activities especially those which requires companions or members. We cannot deny the fact that there are still people who are willing to come out and do sports in a group. However, most of the time they do not have enough members to conduct the sport. This situation can lead to discouragement and stopping them from doing any more sports activity just because of insufficient team member. This situation can lead to discouragement and stopping them from doing any more sports activity just because of insufficient team members. The Sports Team Finder is a mobile application that helps the students in Universiti Tun Hussein Onn Malaysia (UTHM) to reach other people who has the same intention, i.e., to get team members. Students can use this application to find team members for team-oriented games such as basketball, football, netball, etc. The aim is to design an application where it motivate users to engage other people through sports and meeting new friends along the way. The application is able to function properly and successfully gather users with similar interest together. It has shown that the application has caused an improvement of sport involvement among students in UTHM.